2007
DOI: 10.1007/s11695-007-9243-7
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-Binding Protein Plasma Levels and Liver TNF-Alpha Gene Expression in Obese Patients: Evidence for the Potential Role of Endotoxin in the Pathogenesis of Non-Alcoholic Steatohepatitis

Abstract: NAFLD patients have elevated plasma levels of LBP and they are further increased in patients with NASH. This increase is related to a rise in TNF-alpha gene expression in the hepatic tissue which supports a role for endotoxemia in the development of steatohepatitis in obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(101 citation statements)
references
References 38 publications
5
95
0
1
Order By: Relevance
“…However, there is evidence suggesting that other endogenous factors might be involved in its pathogenesis. These include obstructive sleep apnea-induced hypoxia [71,72], by-products of both carbohydrate [73][74][75][76][77] and lipid metabolism [78][79][80], and gut-derived bacterial toxins [81,82]. Furthermore, nonoxidative metabolites of ethanol [19,83,84], methanol/formaldehyde [27,85,86], and nitrosative stressors [87,88] may also contribute to NAFLD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence suggesting that other endogenous factors might be involved in its pathogenesis. These include obstructive sleep apnea-induced hypoxia [71,72], by-products of both carbohydrate [73][74][75][76][77] and lipid metabolism [78][79][80], and gut-derived bacterial toxins [81,82]. Furthermore, nonoxidative metabolites of ethanol [19,83,84], methanol/formaldehyde [27,85,86], and nitrosative stressors [87,88] may also contribute to NAFLD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory cytokines facilitate immune cell chemotaxis and tissue infiltration which potentiates hepatic injury (Day and James, 1998b;Marra et al 2008). Tumor necrosis factor-␣ (TNF␣) and interleukin-6 (IL-6) may be important therapeutic targets in NAFLD (Crespo et al 2001;Ruiz et al 2007;Koca et al 2008;Mas et al 2009;Wieckowska et al 2008), so it is noteworthy that H 2 S reduced these inflammatory markers as well as prostaglandin E2, intercellular adhesion molecule 1 (ICAM-1), and nitric oxide (NO) in both the liver and in immune cells (Hu et al 2007;Kang et al 2009). H 2 S also inhibited polymorpholeukocyte accumulation (Sivarajah et al 2009) and mitigated homocysteine-induced inflammation (Sen et al 2011).…”
Section: Inflammationmentioning
confidence: 99%
“…H 2 S induced sinusoidal constriction, increased intrahepatic resistance, and led to heterogeneous perfusion and leukocyte trapping in the liver sinusoids following endotoxin challenge (Norris et al 2013a). Since gutderived endotoxin is also a recognized pathogenic mediator in NAFLD (Day and James 1998a;Ruiz et al 2007;Tilg and Moschen 2010), more studies are needed to determine the role of H 2 S in the regulation of hepatic vascular tone and function in NAFLD.…”
Section: Portal Hypertension and Hepatic Microcirculatory Dysfunctionmentioning
confidence: 99%
“…Adipogenic transformation may play a crucial role in the progression of simple steatosis to NASH in two ways. It has been shown that NEFA, e.g., palmitate, the end product of de novo lipogenesis (Nguyen et al 2008), act as mediators of inflammation in adipose tissue in obesity and that LPL hydrolytic activity is a key mediator of macrophage activation and cytokine secretion (Guerra Ruiz et al 2007). LPL is also proposed to participate in the process of macrophage recruitment in adipose tissue by enhancing endothelial adhesion of monocytes (Li and Renier 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, several studies have reported that obese patients with NASH had a significant increase in liver TNF-α mRNA when compared to obese controls without NASH (Crespo et al 2001;Guerra Ruiz et al 2007;Cayón et al 2008). Moreover, a 4.6-fold increase was discovered in TNF-α expression in morbidly obese patients with severe steatosis and NASH compared to those with a histologically scored diagnosis of only severe steatosis (Bertola et al 2010).…”
Section: Discussionmentioning
confidence: 99%